Lichen sclerosus: a clinical study - Kshetrimayum, Sandhyarani; Thokchom, Nandakishore Singh; ., Vanlalhriatpuii; Bishurul Hafi, N. A. (International Journal of Research in Dermatology, 2017)
Background: Lichen sclerosus (LS) is a chronic inflammatory disorder that preferentially affects the anogenital region and rarely extra genital sites. It is more common in women and has a bimodal peak of incidence. The objective of the study was to document the clinical, demographic pattern and associated systemic diseases of lichen sclerosus (LS) among patients attending skin OPD, RIMS, Imphal. Methods: All patients presenting with signs and symptoms suggestive of lichen sclerosus (LS) were studied for a period of 24 months from March 2014 to February 2016. Clinical examination and relevant investigations including histopathology were performed. Results: A total of 54 patients were studied (17 males and 37 females). M:F ratio was 1:2.2. Majority belonged to 25-44 years age group (29.6%). Ano-genital LS comprised 81.4% of the cases. All patients presented with hypopigmented atrophic plaque (100%). The commonest site was prepuce (53.3%) in males and labia majora, labia minora and clitoris (62%) in females. There were 2 cases of balanitis xerotica obliterans (BXO). Ten patients (18.6%) had extragenital LSA and the sites involved were trunk, waist and extremities. Associated systemic diseases were detected in 6 patients. Conclusions: Lichen sclerosus is not an uncommon disease. Varied presentations ranging from asymptomatic white patch to severe inflammation and scarring were noted. Complications especially with genital involvement can be prevented by early diagnosis and adequate treatment. Screening for associated systemic disease may prove useful.